Ulama Dan Perannya Dalam Masyarakat Multikultural di Desa Sumber Jaya Kecamatan Sumber Marga Telang Kabupaten Banyuasin - Mohammad Saiful Rizal; Sri Suriana; Nurfitri Hadi (Tanjak: Sejarah dan Peradaban Islam, 2022)
This study describes the role of ulama in a multicultural society in Sumber Jaya Village, Sumber Marga Telang District, Banyuasin Regency. This type of research is qualitative using field research methods, with a qualitative approach. The main points of this research are: 1) How is the life of the multicultural community in Sumber Jaya Village, Sumber Marga Telang District, Banyuasin Regency: 2) What is the role of ulama in maintaining multicultural community harmony in Sumber Jaya Village, Sumber Marga Telang District, Banyuasin Regency?.. This study uses Soejono Soekamto's theory where the role is more pressing on the side of a person who must put himself in a situation that forces him to act according to his wishes and responsibilities as an individual in society. The results of this study found that the ulama played a very important role in maintaining the harmony of the multicultural community in Sumber Jaya Village and fulfilling their roles as preachers, educators and providing advice and liaison between the community. As for some of the efforts of the ulama and religious leaders and village officials in maintaining harmony by holding regular Village Clean Activities, helping maintain order when there are religious activities, and social care involving the entire community of Sumber Jaya village.